Uncovering the mechanism of Kang-ai injection for treating intrahepatic cholangiocarcinoma based on network pharmacology, molecular docking, and in vitro validation - Song, Fei; Lu, Chang-Liang; Wang, Cheng-Gui; Hu, Chen-Wei; Zhang, Yu; Wang, Tian-Lun; Han, Lu; Chen, Zhong (Frontiers in Pharmacology, 2023)
Objective: Kang-ai injection (KAI) has been widely used in solid tumors as an adjuvant treatment. However, the precise mechanism of its anti-tumor activity in intrahepatic cholangiocarcinoma (ICC) remains unclear. To identify the anti-tumor actives, critical targets, and probable pharmacological mechanism of KAI in ICC, a network pharmacology-based strategy, together with molecular docking and in vitro validation was carried out. Methods: A KAI-compound-target-ICC network was created to describe the connections between active KAI compounds and potential targets based on available datasets. GO, KEGG enrichment analysis, and PPI network were performed to discover crucial bioactive ingredients, potential targets, and signaling pathways. The patterns of interactions between hub targets and components were visualized via molecular docking. Eventually, the findings were further validated by in vitro experiments. Results: 87 active ingredients of KAI and 80 KAI-ICC-related targets were screened. GO and KEGG enrichment analyses reveal that the PI3K-AKT signaling pathway may play a crucial role in ICC pharmacotherapy. 10 core target genes, including AKT1 and IL1β, were screened by the PPI network and its sub-networks. Molecular docking experiments found that the target proteins AKT1 and IL1β can bind stably to the active ingredient of KAI. Cell experiments demonstrated that KAI might suppress the proliferation of ICC cell lines by blocking the PI3K/AKT signaling pathway, confirming the above prediction. Conclusion: This research illustrates KAI's biological activity, potential targets, and molecular mechanisms in treating ICC. It also provides a promising strategy for revealing the scientific underpinning and therapeutic mechanisms of herbal formulations used to treat ICC.